Self-Talk Functions: Portrayal of an Elite Power Lifter. Issue 2 (October 2014) - Cutton, David M.; Hearon, Christopher M.
The study presents the results of a case study with a repeated data collection design: a recent and former world champion power lifter provided weekly e-mails, during approximately 6 mo. of training and competition, with a description of his 'self-determined self-talk.' The instruction used for self-talk (ST) mentioned its associations with emotions, staying focused, maintaining motivation, and improving exercise skills. The obtained e-mails were coded using categories indicating functions of 'self-determined self-talk' mainly based on previous literature. The frequency of the functions during training and competition were compared and discussed following the qualitative research tradition.